2020
DOI: 10.3390/v12090968
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Heterologous Prime-Boost Vaccination with H3N2 Influenza Viruses in Pre-Immune Individuals: Studies in the Pig Model

Abstract: In a previous study in influenza-naïve pigs, heterologous prime-boost vaccination with monovalent, adjuvanted whole inactivated vaccines (WIV) based on the European swine influenza A virus (SwIAV) strain, A/swine/Gent/172/2008 (G08), followed by the US SwIAV strain, A/swine/Pennsylvania/A01076777/2010 (PA10), was shown to induce broadly cross-reactive hemagglutination inhibition (HI) antibodies against 12 out of 15 antigenically distinct H3N2 influenza strains. Here, we used the pig model to examine the effica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 69 publications
(91 reference statements)
1
8
0
Order By: Relevance
“…In the case of group 3xMOV, pigs were challenged with a heterologous swIAV of the same HA subtype as the vaccine strain, a situation that is believed to predispose for “vaccine-associated enhanced respiratory disease” (VAERD) [ 66 ]. However, in line with other European swine vaccination studies [ 18 , 21 24 , 52 , 53 ], there were no significant differences in macroscopic lesion scores and histopathological findings among groups. As to group 3xMOV, the VAERD phenomenon might have been abrogated by the NI antibodies against G18 [ 67 ].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In the case of group 3xMOV, pigs were challenged with a heterologous swIAV of the same HA subtype as the vaccine strain, a situation that is believed to predispose for “vaccine-associated enhanced respiratory disease” (VAERD) [ 66 ]. However, in line with other European swine vaccination studies [ 18 , 21 24 , 52 , 53 ], there were no significant differences in macroscopic lesion scores and histopathological findings among groups. As to group 3xMOV, the VAERD phenomenon might have been abrogated by the NI antibodies against G18 [ 67 ].…”
Section: Discussionsupporting
confidence: 87%
“…As an example, our data support the use of a multivalent vaccine (TIV or BIV), instead of the monovalent MOV vaccine, for the third vaccination, as this may boost antibody titers against H3 and human-like H1 swIAVs. Combinations of European and North American swIAV vaccines would results in an increased genetic and antigenic distance between vaccine strains and might also broaden the antibody responses [ 52 , 53 ] (Chepkwony et al, unpublished observations). Finally, prime-boost regimens with a LAIV followed by a WIV booster were shown to result in higher T cell responses than 2 WIV administrations [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated the immunological impact of prior influenza exposure on vaccine efficacy in large animal models. Chepkwony et al demonstrated that prior H3N2 exposure followed by intramuscular immunization with whole inactivated heterologous H3N2 vaccine induced stronger and broader antibody responses (43). Ferrets with pre-existing immune responses influenced recombinant H2 antibodies following vaccination (44).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have evaluated the immunological impact of prior influenza exposure on vaccine efficacy in large animal models. Chepkwony et al demonstrated that prior H3N2 exposure followed by intramuscular immunization with whole inactivated heterologous H3N2 vaccine induced stronger and broader antibody responses 37 . Ferrets with pre-existing immune responses influenced recombinant H2 antibodies following vaccination 38 .…”
Section: Discussionmentioning
confidence: 99%